Optimizing Nutrition Care Management at Nutrition Care Center (NCC) - Wijayanti, Rossalina; Dewi, Riskha Dora Candra; Farlida, Sustin; Nuraini, Novita (International Journal of Healthcare and Information Technology, 2024)
In nutrition care services, the creation and storage of medical records at the Nutrition Care Center (NCC) are still relatively simple and paper-based or manual. Additionally, management challenges, in the form of system constraints, are one of the obstacles to healthcare management at NCC. Therefore, there is a need for optimizing healthcare management at NCC. The aim of this study is to optimize nutrition care management at the NCC clinic through the use of EMR (Electronic Medical Records) facilitated by QR Codes and the implementation of a Whatsapp Bot. The results indicate that optimizing Nutrition Care Management through the Implementation of EMR with QR Codes and Whatsapp Bot simplifies nutritionists' access to previous client allergy and therapy history in one view and facilitates clients in accessing their medical record number without a physical card. This research has also designed a system that can be used both through web and mobile platforms